SECURITY CONTROL SYSTEM ON GATE, LIGHT AND ALARM FOR WAREHOUSE MONITORING OR ARDUINO UNO BASED FACTORY WITH LABVIEW VISUALIZATION - Setiawan Setiawan Setiawan (Universitas 17 Agustus 1945 Jakarta, 2020)
In the industrial world, time and cost efficiency is very important in achieving productivity. Almost all production has used an automatic system, but non-production equipment in this industrial environment is still controlled manually, one of which is equipment owned by security. Gate operations, activating street lights in the warehouse or factory area, and monitoring security are done manually. Making a control system with an Arduino Uno microcontroller in the form of LDR, PIR, and Limit Switch sensors input with output in the form of street lights, alarms, indicator lights and automatic gates with visual displays in the form of animation on PC / HMI with Labview software The LDR sensor is used to check the light, where when it is bright the lights will turn off and when it is dark the lights will turn on. The PIR sensor is used to check for human movement. The detected movement produces an output in the form of an alarm on the buzzer and an indicator light that will light up, and the gate will be closed automatically. Limit Switch functions as a limit for opening and closing the gate. With this control system, it is hoped that security can control and monitor every activity in only one place so that security activities can be more optimal and efficient.